2010
DOI: 10.1002/pmic.200900572
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of colonic mucosa in a rat model of irritable bowel syndrome

Abstract: Irritable bowel syndrome (IBS) is one of the most common functional disorders of the gastrointestinal tract. It is characterized by abdominal pain and changes in bowel habits. Various studies have investigated the pathophysiologic processes underlying IBS, but the mechanism remains poorly understood. In the present study, we established an IBS model and identified differentially expressed proteins in colon tissue of IBS rats compared with healthy controls by 2-D gel electrophoresis, MALDI-TOF-MS, and Western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 62 publications
1
22
0
1
Order By: Relevance
“…In the present study, eight differential protein species related to immune response were down-regulated in the treatment group. HMGB1 and HMGB3 serve as immunogenic nucleic acids binding proteins that are generally involved in the nucleic acid receptor-mediated activation of innate immune responses [62,63]; MYO1G is a plasma membrane-associated class I myosin contributing to T-cell activation [64]; SERPINB5 is a tumor suppressor that plays a role in protein binding [65]; IRF3 is a transcription factor that plays distinct role in innate antiviral response [66]; GIT2 is one of regulators of G protein-coupled receptor (GPCR), and loss of GIT2 in vivo leads to an immunodeficient state [67]; HMHA1 is a major target of immune responses also playing a role in T-cell activation [68]; and PLD1 contributes to the essential function of macrophages for protecting against a wide variety of invading microorganisms [69]. Down-regulation of these proteins in the treatment group suggests that, the immunity of gut is under low condition in ammonia-exposed broilers, which increases possibilities of bacterial or viral infection and probably leads to lower growth rate.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, eight differential protein species related to immune response were down-regulated in the treatment group. HMGB1 and HMGB3 serve as immunogenic nucleic acids binding proteins that are generally involved in the nucleic acid receptor-mediated activation of innate immune responses [62,63]; MYO1G is a plasma membrane-associated class I myosin contributing to T-cell activation [64]; SERPINB5 is a tumor suppressor that plays a role in protein binding [65]; IRF3 is a transcription factor that plays distinct role in innate antiviral response [66]; GIT2 is one of regulators of G protein-coupled receptor (GPCR), and loss of GIT2 in vivo leads to an immunodeficient state [67]; HMHA1 is a major target of immune responses also playing a role in T-cell activation [68]; and PLD1 contributes to the essential function of macrophages for protecting against a wide variety of invading microorganisms [69]. Down-regulation of these proteins in the treatment group suggests that, the immunity of gut is under low condition in ammonia-exposed broilers, which increases possibilities of bacterial or viral infection and probably leads to lower growth rate.…”
Section: Discussionmentioning
confidence: 99%
“…Keratin 8 (KRT8) and keratin 18 (KRT18) are the major cytoskeletal intermediate filaments (IFs) in the intestinal epithelia (Ding et al, 2010). KRT8 is the major type II keratin in the small and large intestine, along with type I keratins KRT18, 19, or 20 dependent on the cell and individual tissue.…”
Section: Continued) Differentially Expressed Proteins In the Colon Mmentioning
confidence: 99%
“…CK8 overexpression has been shown to induce degradation and remodelling of actin and tubulin [14-17]; its negative correlation with TJ-related proteins has also been reported [18]. Moreover, in our previous study, CK8 expression was found to be significantly increased in the ileocaecal intestinal mucosa of stressed IBS rats [19]. Furthermore, we found increased expression of CK8 in colonic epithelial cells of rats with IBS, along with the remodelling of actin and dysfunctional distribution of claudin-1 and ZO-1.…”
Section: Introductionmentioning
confidence: 99%